PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, ETOS KERJA, DAN DISIPLIN KERJA GURU TERHADAP KUALITAS LAYANAN SEKOLAH DI SD GUGUS 7 KECAMATAN CIKUPA KABUPATEN TANGERANG - Selviyana Maulina Wardani; Siti Zubaidah; Rian Sri Rahayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of transformational leadership, work ethic, and teachers' work discipline on school service quality in Cluster 7 Public Elementary Schools, Cikupa District, Tangerang Regency. The study employed a quantitative approach using an explanatory research design. The research population consisted of 159 teachers, with a sample of 114 teachers. Data were collected using a Likert-scale questionnaire and analyzed through normality, linearity, homogeneity, and multiple linear regression analyses. The results revealed that transformational leadership had a positive and significant effect on school service quality (β = 0.366; t = 7.073; p < 0.05). Work ethic also had a positive and significant effect (β = 0.242; t = 4.932; p < 0.05), as did teachers' work discipline (β = 0.206; t = 4.178; p < 0.05). Simultaneously, transformational leadership, work ethic, and work discipline had a positive and significant effect on school service quality (F = 444.306; p < 0.001), with a coefficient of determination (R²) of 0.924. This indicates that 92.4% of the variance in school service quality can be explained by the three independent variables. Transformational leadership was identified as the most dominant predictor of school service quality. These findings highlight the importance of strengthening school leadership, improving teachers' work ethic, and enhancing work discipline to improve the quality of educational services